Investigation of chronotherapeutic effects of amphotericin B administered to mice infected with Candida albicans - GÜRBÜZ, BURÇAK; SOYOĞUL GÜRER, ÜMRAN (TAYLOR & FRANCIS LTD, 2013)
In this study, mice were infected with Candida albicans at 07:00 h or 19:00 h. After 24 h, the subgroups of mice received either 0.2/ml saline (as control) or one of two doses (0.5 or 1.0 mg/kg) of amphotericin B (AmB) at 0 h or 12 h for three consecutive days. A second set of uninfected mice received a single dose of either saline or AmB (5 mg/kg) at 0 h or 12 h for 4 days to study only about nephrotoxicity. For uninfected controls and AmB-treated (5 mg/kg) mice, serum blood urea nitrogen (BUN), creatinine and total protein tended to be higher at 0 h vs. 12 h, as was the histopathology score in treated mice (3.60 vs. 1.20). Serum levels changed in treated mice when compared to the control mice. The BUN levels increased whereas serum creatinine levels decreased at 12 h compared to 0 h. C. albicans colony forming units per milliliter (CFU/ml) was high in the kidneys of infected mice. Compared with the control, after treatment for 3 days with 0.5 mg AmB lowered CFU by 48% at 0 h and by 75% at 12 h. However, for the higher dose 1.0 mg AmB, CFU was lowered more or less equally at both test times: 51% at 0 h and 46% at 12 h.
Keywords: chronobiology; amphotericin B; mice; Candida albicans; nephrotoxicity; INDUCED NEPHROTOXICITY; THERAPEUTIC-EFFICACY; TOXICITY; PHARMACOKINETICS; GENTAMICIN; MODEL; CILOFUNGIN; TIME